Celestial Aspects of Hittite Religion: An Investigation of the Rock Sanctuary Yazilikaya - Zangger, Eberhard; Gautschy, Rita (Journal of Skyscape Archaeology, 2019)
Regular celestial events assumed remarkable significance for the cultic rituals of the Hittite civilisation (c. 1600-1180 BC) in central Asia Minor. Numerous texts found at the capital Hattuša relate to solar deities and celestial divination reminiscent of Old Babylonian astronomical and astrological practices. Here we suggest that the rock sanctuary of Yazilikaya, which was considered one of the holiest places in the Hittite kingdom, had a calendrical function. It contains more than 90 rock-cut reliefs, dating to the second half of the thirteenth century BC, of deities, humans, animals and mythical figures. The reliefs in Chamber A are arranged in groups to mark the days, synodic months and solar years. Using this system, the Hittite priests were able to determine when additional months were required to keep lunar and solar years aligned. The astronomical and astrological interpretation of Yazilikaya serves as a point of departure for a brief re-examination of celestial aspects in Hittite religion.